The Effect of Quality of Human Resources on Economic Growth in Malang Regency - Rismawati Rismawati (Trunojoyo University of Madura, 2022)
Performance as one of the main points in the economic development of a country, this is also known as growth. The expected economic growth must of course be of quality, where there is a growth that occurs and has a sensitivity to unemployment and existing poverty. This study aims to determine the influence of the Quality of Human Resources in Economic Growth in Malang Regency. This study uses secondary data analysis which aims to provide an explanation of the role of the quality of human resources on economic growth in Malang district in the 2011 to 2020 fiscal year. The secondary data consists of (1) economic growth seen from constant price GRDP, (2) population in productive age, (3) the proportion of the population aged 10 years who have a high school education and, (4) Life Rate and Expectations at birth. The data is processed using Multiple Linear Regression. The results in the study show that (1) the proportion of the population of productive age has a positive and insignificant effect on economic growth, (2) high school education and above has a positive and significant effect on economic growth, (3) health life expectancy has no significant effect on economic growth. The quality of human resources as measured by using three variables as independent variables has a significant effect on economic growth. The influence of these three variables is very significant both in their position as individual variables (independently) or jointly or simultaneously has a significant effect on economic growth.